Low temperature firing and microwave dielectric properties of Bi4-xGe3O12-1.5x ceramics - Ma, Xing-Hua; Kweon, Sang-Hyo; Nahm, Sahn; Kang, Chong-Yun; Yoon, Seok-Jin; Kim, Young-Sik (ELSEVIER SCI LTD, 2017)
Dense Bi4Ge3O12 ceramics sintered at 850 degrees C had a relative permittivity (epsilon(r)) of 15.7, temperature coefficient of resonant frequency (tau(f)) of 24.2 ppm/degrees C, and quality factor (Qxf) of 28,361 GHz. However, because of the existence of Bi12GeO20 as a secondary phase, the microwave dielectric properties of Bi4Ge3O12 would be degraded. Therefore, to avoid the formation of the Bi12GeO20 secondary phase, Bi2O3-deficient ceramics with 0.1<_x<_0.6 were sintered at 850 degrees C. A single phase of Bi3.6Ge3O11.4 (x=0.4) ceramic sintered at 850 degrees C for 5 h without any secondary phase exhibited suitable microwave dielectric properties for a ceramic substrate: epsilon(r)=14.9, tau(f) =-9.5 ppm/degrees C, and Qxf=53,277 GHz.
Keywords: BISMUTH-GERMANATE; GLASS; DETECTORS; POROSITY; MN